(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is dedicated to exploring effective reading strategies for academic texts. It presents key methods suitable for students, including previewing, skimming, annotation and note-taking, summarization, questioning, and metacognitive strategies. Each strategy is explained in detail and supplemented with practical exercises, examples, and interactive suggestions. The article aims to help students improve focus, enhance memory, strengthen comprehension, and develop independent reading skills. Additionally, it provides teachers with practical methodological guidance to support classroom instruction and promote active learning.